The body code : unlocking your body's ability to heal itself - Nelson, Bradley (St. Martin's Essentials, 2023)
"A powerful new approach to natural, intuitive whole-body healing. The Body Code is a truly revolutionary method of holistic healing. Dr. Bradley Nelson, a globally renowned expert in bioenergetic medicine, has spent decades teaching his powerful self-healing method and training practitioners around the globe, but this is the first time his system of healing will be available to the general public in the form of The Body Code. The Body Code is based on the simple premise that the body is self-healing and knows what it needs in order to thrive and flourish. The Body Code method allows readers to tap into this inner knowing, and find imbalances in 6 key areas - Energies, Circuits and Systems, Toxicity, Nutrition and Lifestyle, Misalignments, and Pathogens - that are the root causes of our physical, mental and emotional issues. By identifying and releasing these imbalances, readers become empowered to activate their body's innate healing power. Filled with powerful first-hand accounts of healing, hundreds of color illustrations, and concrete, actionable steps, The Body Code is a road map to healing based in deep study of the human body, time-proven ancient practices, and the unlimited power of the subconscious mind"--